Understanding the biology, morbidity and social contexts of adolescent tuberculosis: a prospective observational cohort study protocol (Teen TB) - Anneke C Hesseling; Alex Doruyter; Elizabeth Whittaker; James A Seddon; Brian W Allwood; Graeme Hoddinott; David A J Moore; Stephanus Malherbe; H Simon Schaaf; Gert Van Zyl; Marieke M van der Zalm; Jeremi Swanepoel; et al. (BMJ Open)
Introduction A considerable burden of the tuberculosis (TB) epidemic is found in adolescents. The reasons for increased susceptibility to TB infection and higher incidence of TB disease in adolescence, compared with the 5–10 years old age group, are incompletely understood. Despite the pressing clinical and public health need to better understand and address adolescent TB, research in this field remains limited.Methods and analysis Teen TB is an ongoing prospective observational cohort study that aims to better understand the biology, morbidity and social context of adolescent TB. The study plans to recruit 50 adolescents (10–19 years old) with newly diagnosed microbiologically confirmed pulmonary TB disease and 50 TB-exposed controls without evidence of TB disease in Cape Town, South Africa, which is highly endemic for TB. At baseline, cases and controls will undergo a detailed clinical evaluation, chest imaging, respiratory function assessments and blood collection for viral coinfections, inflammatory cytokines and pubertal hormone testing. At 2 weeks, 2 months and 12 months, TB disease cases will undergo further chest imaging and additional lung function testing to explore the patterns of respiratory abnormalities. At week 2, cases will complete a multicomponent quantitative questionnaire about psychological and social impacts on their experiences and longitudinal, in-depth qualitative data will be collected from a nested subsample of 20 cases and their families.Ethics and dissemination The study protocol has received ethical approval from the Stellenbosch University Health Research Ethics Committee (N19/10/148). The study findings will be disseminated through peer-reviewed publications, academic conferences and formal presentations to health professionals. Results will also be made available to participants and caregivers.